Comparison of data collected with a commercial thermo-hygrometer and with a DHT-11 sensor associated with an Arduino board and its potential for use in scientific research and teaching - Mariano, Erich de Freitas (2022)
Prototyping platforms allow the researcher to personalize the data collection and its presentation, minimize costs in the purchase of equipment and provide greater integration of knowledge, when used for educational purposes. Given these advantages, in this article we present the data of air temperature and humidity obtained by two different equipment, one commercial and the other built under a free hardware platform, and we discuss the use of similar platforms in research and teaching. When making comparisons between the two mentioned equipment, the statistical tests did not show significant differences between the collected environmental data. In this way, we can employ such platforms without fear. Implementing technologies in science education creates more motivating environments, more attentive and committed students in the development of their work and, therefore, a better performance in evaluations. For when creating and interacting with software or hardware, the student experiences the "experiential continuum", in which he makes decisions about the best way to solve problems. It is in this context that computers, microcontrollers like the one used by Arduino, programming languages and computational thinking are tools to support research and science teaching. However, its use must be made consciously and guided by the teacher, who often does not have adequate training.